The inhibitor of cyclin-dependent kinases, olomoucine II, exhibits potent antiviral properties - Holcakova, Jitka; Tomasec, Peter; Bugert, Joachim J; Wang, Eddie Cy; Wilkinson, Gavin Wg; Hrstka, Roman; Krystof, Vladimir; Strnad, Miroslav; Vojtesek, Borivoj (Antiviral chemistry & chemotherapy, 2010)
BACKGROUND: Olomoucine II, the most recent derivative of roscovitine, is an exceptionally potent pharmacological inhibitor of cyclin-dependent kinase activities. Here, we report that olomoucine II is also an effective antiviral agent. METHODS: Antiviral activities of olomoucine II were tested on a range of human viruses in in vitro assays that evaluated viral growth and replication. RESULTS: Olomoucine II inhibited replication of a broad range of wild-type human viruses, including herpes simplex virus, human adenovirus type-4 and human cytomegalovirus. Olomoucine II also inhibited replication of vaccinia virus and herpes simplex virus mutants resistant to conventional acyclovir treatment. This report is the first demonstration of a poxvirus being sensitive to a cyclin-dependent kinase inhibitor. The antiviral effects of olomoucine II could be observed at lower concentrations than with roscovitine, although both were short-term. A remarkable observation was that olomoucine II, when used in combination with the DNA polymerase inhibitor cidofovir, was able to almost completely eliminate the spread of infectious adenovirus type-4 progeny from infected cells. CONCLUSIONS: Our results show that when targeting two complementary antiviral mechanisms, strongly additive effects could be observed.
Keywords: Protein Kinase Inhibitors; Purines; fyziologie virů; Virus Physiological Phenomena; viry; antivirové látky; Cyclin-Dependent Kinases; inhibiční koncentrace 50; Antiviral Agents; puriny; lidé; cyklin-dependentní kinasy; replikace viru; Inhibitory Concentration 50; inhibitory proteinkinas; Humans; Virus Replication; Viruses